TRADISI BOKA DALAM PERNIKAHAN MASYARAKAT DESA WAEPANDAN SUKU BUTON PERSPEKTIF HUKUM ISLAM DAN HUKUM POSITIF - La Aliman Aririn Sampulawa; Ach Faisol; Dzulfikar Rodafi (Prodi Ahwal syakhshiyyah Fakultas Agama Islam UNISMA, 2022)
Humans are one of God's creatures who were created in the best form. Perfected with reason, mind and lust to vent his lustful desires. For this reason, in meeting their needs, humans are given the ability to live in a relationship with one another. In this case the intended relationship is marriage. It is normal for marriages to take place anywhere, but in practice in some areas there are some differences that are influenced by ethnicity and religion as in the marriage tradition of the Buton people. This study raises the issue of Boka traditional customs at the weddings of the Waepandan village community and the Buton tribe located in Maluku. A village that is predominantly Muslim and has the largest population of Butonese tribes, so this study combines the practice of these traditions in view of Islamic law and applicable positive law. This research was compiled based on the results of field observations with the help of traditional shops as the main informant for the credibility and authenticity of the information served. So that a sequence of customary rules was found which was completed by traditional leaders through the approach of Islamic law and positive lawKeywords: Marriage, Tradition, Boka, Law